Correction: Asymptomatic Plasmodium vivax malaria in the Brazilian Amazon: Submicroscopic parasitemic blood infects Nyssorhynchus darlingi. - Negelected Tropical Diseases Genetics Staff (PLoS Neglected Tropical Diseases, 2023)
[This corrects the article DOI: 10.1371/journal.pntd.0009077.].